2017
DOI: 10.1093/jxb/erx029
|View full text |Cite
|
Sign up to set email alerts
|

MdHB1 down-regulation activates anthocyanin biosynthesis in the white-fleshed apple cultivar ‘Granny Smith’

Abstract: Coloration in apple (Malus×domestica) flesh is mainly caused by the accumulation of anthocyanin. Anthocyanin is biosynthesized through the flavonoid pathway and regulated by MYB, bHLH, and WD40 transcription factors (TFs). Here, we report that the HD-Zip I TF MdHB1 was also involved in the regulation of anthocyanin accumulation. MdHB1 silencing caused the accumulation of anthocyanin in 'Granny Smith' flesh, whereas its overexpression reduced the flesh content of anthocyanin in 'Ballerina' (red-fleshed apple). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 80 publications
4
61
0
Order By: Relevance
“…In this study, the core set of candidate genes for anthocyanin and PA accumulation included four R2R3-MYB genes: PcMYB3, PcMYB86, PcMYB111 and PcMYB114, which were strongly positively correlated with anthocyanins and PAs. This result provides evidence that MdUFGT indirectly by interacting with MdMYB10, MdbHLH3, and MdTTG1 [50]. Consistent with the results in apple, silencing of RhHB1 in rose led to higher anthocyanin levels in the petals [51].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the core set of candidate genes for anthocyanin and PA accumulation included four R2R3-MYB genes: PcMYB3, PcMYB86, PcMYB111 and PcMYB114, which were strongly positively correlated with anthocyanins and PAs. This result provides evidence that MdUFGT indirectly by interacting with MdMYB10, MdbHLH3, and MdTTG1 [50]. Consistent with the results in apple, silencing of RhHB1 in rose led to higher anthocyanin levels in the petals [51].…”
Section: Discussionsupporting
confidence: 86%
“…Overexpression of MdHB1 led to reduced anthocyanin accumulation in apple flesh. MdHB1 was found to repress the transcription of MdDFR and MdUFGT indirectly by interacting with MdMYB10, MdbHLH3, and MdTTG1 [37]. Consistent with the results in apple, silencing of RhHB1 in rose led to higher anthocyanin levels in the petals [38].…”
Section: Discussionsupporting
confidence: 79%
“…In a recent study, a tomato HD-ZIP I family gene designated LeHB1 was shown to play key roles in carpel development and fruit maturation 15 . MdHB1 , the homologous gene of LeHB1 in apple, has been reported to be involved in the regulation of anthocyanin accumulation 63 . In our study, some VvHB genes ( VvHB62 , VvHB54 and VvHB7 ) belonging to the HD-ZIP I subfamily showed markedly differential expression during ovule development between seedless and seeded grape.…”
Section: Discussionmentioning
confidence: 99%